2023
DOI: 10.3390/jpm13020247
|View full text |Cite
|
Sign up to set email alerts
|

Love Addiction, Adult Attachment Patterns and Self-Esteem: Testing for Mediation Using Path Analysis

Abstract: Love addiction is a dysfunctional relational modality that takes on the addiction characteristics and which, for the individuals who suffer from it, can have a negative and pervasive impact on various areas of functioning. The objective of this research was the analysis the factors that can be associated with love addiction, particularly focusing on adult attachment patterns and self-esteem. A sample group of 300 individuals who declared themselves to have a romantic relationship was involved in this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…This is in line with existing evidence. For example, previous research has shown that childhood physical abuse is associated with adult anxious attachment (Muller et al, 2008), which in turn presents a significant and positive relationship with love addiction (Gori et al, 2023). Furthermore, childhood emotional abuse has been found to be associated with rejection sensitivity in adulthood (Hernandez et al, 2016), as well as different areas of personality dysfunction, including dependent pathology (see Li et al, 2020 for a review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with existing evidence. For example, previous research has shown that childhood physical abuse is associated with adult anxious attachment (Muller et al, 2008), which in turn presents a significant and positive relationship with love addiction (Gori et al, 2023). Furthermore, childhood emotional abuse has been found to be associated with rejection sensitivity in adulthood (Hernandez et al, 2016), as well as different areas of personality dysfunction, including dependent pathology (see Li et al, 2020 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Love addiction can lead to a lower quality of life given the negative social, security, or legal consequences (Sussman, 2010) and has also been associated with worse psychological outcomes, such as alexithymia and depression (Speranza et al, 2004). Furthermore, individuals involved in pathological love have lower levels of self-esteem and self-directedness than individuals with healthy relationships (Acevedo & Aron, 2009; Gori et al, 2023; Sophia et al, 2009). Given the numerous negative consequences and impact that this condition has on the lives of individuals who suffer from it, the study of the risk factors involved in the onset of love addiction is of considerable importance.…”
Section: Childhood Trauma and Love Addictionmentioning
confidence: 99%
“…The Traumatic Experiences Checklist (TEC) [ 10 , 34 ] is a self-report measure designed for the assessment of 29 types of potentially traumatizing events. It consists of 29 items scored on a true-false form; for the events that occurred, the participant is also asked to rate the extent of the impact on a 5-point Likert scale (from 1 = “none” to 5 = “an extreme amount”).…”
Section: Methodsmentioning
confidence: 99%
“…Gori and colleagues [ 5 ] elaborated an explanation of the relationship among these variables in gambling disorders by integrating previous scientific evidence [ 6 , 7 ]. Therefore, emphasis was placed on the experiences with caregivers and insecure attachment, and negative developmental environments were considered risk factors for addiction occurrence [ 8 , 9 , 10 , 11 , 12 ]. These attachment failures might represent the source of childhood traumatic experiences [ 13 ] and deficits in emotion regulation skills [ 14 ], with difficulty modulating, processing, and communicating emotions (i.e., alexithymia; [ 15 ]) as a consequence; this condition, in turn, could lead to a defensive withdrawal into dissociated mental states to cope with painful emotions [ 16 , 17 , 18 , 19 , 20 , 21 ], which has been associated both theoretically and empirically with addictive behaviors [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these criteria include an excessive amount of time spent on the relationship and, as a result, disengagement from social and work life, as well as attachment problems. In brief, a phenomenological framing of AD in relationships may have the following characteristics: fear of being abandoned and a need for control over the relationship; inability to cope with loneliness and difficulties with separation [5]; emotion dysregulation [6]; feeling undeserving of love as a result of low self-esteem and self-confidence [7]; complete dedication to the partner and total acceptance [8]; and a tendency towards isolation and obsessive thoughts [9].…”
Section: Introductionmentioning
confidence: 99%